Lobular Capillary Hemangioma in the Posterior Trachea: A Rare Cause of Hemoptysis - Ford Turner Amy; Diaz-Guzman Enrique (Case Reports in Pulmonology)
Lobular capillary hemangiomas (LCH) have been cited in the literature as a rare potential cause for recurrent hemoptysis. They are mostly associated with cutaneous and mucosal surfaces. Rarely do they affect the trachea and associated airways in adults. Lobular capillary hemangiomas can be associated with previous trauma to the airway; however, drugs, hormonal shifts, viral oncogenes, production of angiogenic factors, and cytogenetic clonal deletion abnormalities can also influence these lesions. We document a case of a posterior wall tracheal hemangioma with associated recurrent hemoptysis in a 22-year-old male on testosterone therapy. An LCH attached to the posterior tracheal wall can be technically difficult to remove due to risk of perforation and bleeding. There have been no cases documented of posterior wall LCH.